ANALISIS ETOS KERJA PETANI KARET TERHADAP PENDAPATAN DALAM PEMENUHAN KEBUTUHAN KELUARGA DITINJAU PERSPEKTIF EKONOMI ISLAM - Nazila, Hikmatun (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2024)
This research was motivated by indications that the income of rubber farmers in Tempapan Hulu Village, Galing District was insufficient, apart from that, farmers' expenditure was greater, which gave rise to several problems related to the work ethic of rubber farmers regarding income in meeting the needs of families in the village. The theories used in this research are: 1) work ethic, 2) income, 3) fulfillment of needs. The aim of this research is to determine the work ethic of rubber farmers on income in meeting family needs from an Islamic economic perspective. The method used by researchers is qualitative and the data collection techniques used are observation, interviews and documentation. The primary data source is 15 informants who are rubber farmers in Tempapan Hulu Village, Galing District. Where the data analysis techniques used are data reduction, data display, and drawing conclusions and the data validity techniques used are triangulation and member checking. Based on the research results, it shows that rubber farmers in Tempapan Hulu Village have a fairly good work ethic, although there are farmers' work ethic that is not good, such as not being able to say they work hard, lack discipline, are unproductive and lack insight and when viewed from an Islamic economic perspective, rubber farmers have both in terms of honesty, motivation, thriftiness and toughness, as well as in fulfilling family needs which are already good in terms of health level, education level and housing conditions, however, when viewed from the level of income and composition of expenditure, rubber farmers in Tempapan Hulu Village, Galing District only enough to meet primary needs only